HGPRT: enzima recombinante de Schistosoma mansoni e sua ação na imunoterapia durante a esquistossomose murina - Fragelli, Bruna Dias de Lima (Universidade Federal de São Carlos, 2016)
Schistosomiasis is a chronic parasitic disease and neglected, caused by the flatworm Schistosoma sp and affects 240 million people around the world. In Brazil is considered expanding and reaches 19 states. Schistosoma mansoni can evade the host immune response in a way not fully understood. Thus, the search for new drugs for the treatment of schistosomiasis tends to become a new alternative for the control of infections caused by this parasite. The purine bases biosynthetic pathway is a key to drug development, because it is directly related to the maintenance of DNA and RNA synthesis. The recombinant enzyme Hypoxanthine-guanine phosphoribosyltransferase (HGPRT) has an important function in the way of salvation of purine bases. Therefore, this study aimed to evaluate the potential of recombinant enzyme HGPRT treatment (Immunotherapy) in experimental schistosomiasis. The methodology used was Immunotherapy using the enzyme of S. mansoni recombinant HGPRT to treat female mice of the strain Swiss infected with S. mansoni with 3 doses after 28 days of infection. Later it was made the evaluation of egg in feces by the method Kato - Katz, cell count of peritoneal cavity lavage and blood, perfusion for the recovery of adult worms’ door-hepatic system and intestinal mesentery. The results were analyzed using statistical program GraphPad Prism 5.01. Infected animals and treated with the enzyme showed a marked decrease in the number of eggs, which is critical to reducing the morbidity related to parasitosis. There was also a reduction of the parasitic load and the number of eosinophils. The results demonstrate that treatment with recombinant S. mansoni HGPRT enzyme has potential for treatment of schistosomiasis. Thus, these results need to be better investigated to understand which mechanisms are involved in the control of schistosomiasis.
HGPRT: Schistosoma mansoni recombinant enzyme and its action in immunotherapy during murine schistosomiasis
Keywords: Esquistossomose; Imunoterapia; Via de salvação; HGPRT; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOLOGIA CELULAR